2004
DOI: 10.1890/03-0148
|View full text |Cite
|
Sign up to set email alerts
|

Relating Plant Traits and Species Distributions Along Bioclimatic Gradients for 88 Leucadendron Taxa

Abstract: Convergence between species niches and biological traits was investigated for 88 Leucadendron taxa in the Cape Floristic region. First, niche separation analysis was performed to relate species' niche positions/breadths with bioclimatic gradients. These gradients of aridity, seasonality of water availability, heat, and cold stress explained almost all variation in niche distributions. Species present in zones of extreme aridity or temperature exhibited narrower niche breadths than species situated in moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
230
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 268 publications
(248 citation statements)
references
References 47 publications
11
230
1
6
Order By: Relevance
“…While environmental constraints have been studied intensively (Thuiller et al 2004), the importance of biotic interactions for the assemblage of plant communities and coexistence of species, and their underlying mechanisms, are much less understood (Chesson 2000, HilleRisLambers et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…While environmental constraints have been studied intensively (Thuiller et al 2004), the importance of biotic interactions for the assemblage of plant communities and coexistence of species, and their underlying mechanisms, are much less understood (Chesson 2000, HilleRisLambers et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have focused either on ecophysiological processes (Anselmi et al, 2004) or on spatial patterns by the use of statistical relationships (Luoto et al, 2005;Thuiller et al, 2004). We intend here to simultaneously investigate both issues.…”
Section: Introductionmentioning
confidence: 99%
“…More advanced multivariate analyses likely outperform RDA, CCA, and NMDS. For example, co-inertia analyses such as outlying mean index (OMI; Doledec et al 2000, Thuiller et al 2004) have been shown to explain more variance than CCA or RDA. Other recent approaches such as random forest (Breiman 2001) or boosted regression trees (Elith et al 2008) have been shown to provide better prediction than logistic regression for assessing individual species distributions.…”
Section: Discussionmentioning
confidence: 99%